Incorporating rock in surface covers improves the establishment of native pioneer vegetation on alkaline mine tailings - Cross, Adam; Zhong, H.; Lambers, Hans (2021)
Background and aims: Rates of tailings production and deposition around the world have increased markedly in recent decades, and have grown asynchronously with safe and environmentally suitable solutions for their storage. Tailings are often produced in regions harbouring biodiverse native plant communities adapted to old, highly-weathered soils. The highly-altered edaphic conditions of tailings compared with natural soils in these areas will likely select against many locally endemic plant species, making phytostabilisation, rehabilitation or ecological restoration of these landforms challenging.